Patients with Diabetes and Significant Epicardial Coronary Artery Disease Have Increased Systolic Left Ventricular Apical Rotation and Rotation Rate at Rest. Issue 4 (22nd November 2015) - Rasalingam, Ravi; Holland, Mark R.; Cooper, Daniel H.; Novak, Eric; Rich, Michael W.; Miller, James G.; Pérez, Julio E.
Abstract : Objective: The purpose of this study was to determine whether resting myocardial deformation and rotation may be altered in diabetic patients with significant epicardial coronary artery disease (CAD) with normal left ventricular ejection fraction. Design: A prospective observational study. Setting: Diagnosis of epicardial CAD in patients with diabetes. Patients and Methods: Eighty‐four patients with diabetes suspected of epicardial CAD scheduled for cardiac catheterization had a resting echocardiogram performed prior to their procedure. Echocardiographic measurements were compared between patients with and without significant epicardial CAD as determined by cardiac catheterization. Main Outcome Measures: Measurement of longitudinal strain, strain rate, apical rotation, and rotation rate, using speckle tracking echocardiography. Results: Eighty‐four patients were studied, 39 (46.4%) of whom had significant epicardial CAD. Global peak systolic apical rotation was significantly increased (14.9 ± 5.1 vs. 11.0 ± 4.8 degrees, P < 0.001) in patients with epicardial CAD along with faster peak systolic apical rotation rate (90.4 ± 29 vs. 68.1 ± 22.2 degrees/sec, P < 0.001). These findings were further confirmed through multivariate logistic regression analysis (global peak systolic apical rotation OR = 1.17, P = 0.004 and peak systolic apical rotation rate OR = 1.05, P < 0.001). Conclusions: Patients with diabetes with significant epicardial CAD and normal LVEF exhibit an increase in peak systolic apical counterclockwise rotation and rotation rate detected by echocardiography, suggesting that significant epicardial CAD and its associated myocardial effects in patients with diabetes may be detected noninvasively at rest.